Morphological, pathogenic and genetic variability amongst sorghum isolates of Colletotrichum graminicoia from India - A. CHAKRABARTI, V.P. RA0 and R.P. THAKUR, J. LATHA, KUSUM MATHUR, P.K. MUKHERJEE (Indian Phytopathology, 2012)
Summer weather conditions affected the viability of telial inoculum and further diurnal variations in temperature and RH affected the viability of infective secondary sporidia during wheat crop season. Germination of teliospores placed in the rhizosphere of Pennisetum and Sorghum sp.,Â  was reduced by 15.5 and 17.1%, while it improved in the rhizosphere of cucurbits, rice and cotton (27, 22 and 9% respectively) as compared to check buried in the fallow soil. Rhizosphere soil extracts of the same crops were inhibitory to teliospore germination, except that of rice and cucurbits. The off season flodding affected the teliospore germination insignificantly but exposure to sun improved it significantly. The germination of teliospores taken from the intact bunt balls in the various treatments was significantly more as compared to the ones incubated as loose mass. The teliospores of the previous season started germinating with the onset of the wheat crop season and the percent germination further improved. Secondary allantoid sporidia (SAS), were produced in diurnal periodicity. Mid-day and afternoon conditions exerted maximum stress on their formation, germination and survival. Extent of dehydration was measured as percentage of coiled sporidia, which reflected the amount of stress in the environment. This stress was partly mitigated if coiled SAS were shifted to saturated atmosphere.